Análisis del mercado financiero y negociación en las cooperativas de ahorro y crédito del país, año 2017 - Chimbo Tixi, Diana Carolina (2017)
This research project whose title is called "ANALYSIS OF THE FINANCIAL MARKET AND NEGOTIATION IN COOPERATIVES OF SAVINGS AND CREDIT OF THE COUNTRY, YEAR 2017"; has the purpose of carrying out the diagnosis of the Ecuadorian financial market and the bargaining power of the cooperatives in terms of the offer of products, services and other activities; and the internal and external factors that arise in the granting of credits and in the collection of resources taking into account the economic situation that in the majority there is no money to keep but rather the subjects of credit are forced to realize these to undertake business or extend the same giving thus rotation to the money and in several occasions generating informal work for several people; in addition to the approach of the appropriate strategies to attract wealthy partners and thus capitalize to the maximum to be able to offer new lines of credit or larger amounts to specific partners in their payments. The bibliographic research coverage is of the total of the credit unions of Ecuador that are offering their services in national level, many of them for more than fifty years. The 696 savings and credit cooperatives that work in the country have mainly activities of placement, savings capture and credit lines: commercial, housing, educational, microenterprise and consumer, few have other additional and complementary services. Although it is true that 90% of the coverage has the Banks; it is no less true that the coverage of credit unions covers 5%; but, there is a greater number of partners in the middle and lower classes, whose service is greater to people of limited economic resources, cooperative activities are fundamental in the economic development of the country. Descriptive terms: market, financial, cooperatives, analysis, negotiation, services.